Printed Electronics Power Supply for IoT Systems - Guilherme José Esteves Pelayo (2020)
In recent times, connected devices are becoming increasingly more common. Such devices usually referred to as IoT (Internet of Things), are converging to ever small builds. This document aims to deepen the progress in the field of miniaturization of such devices. To achieve this goal a power supply is designed. The project intents to offer an alternative to common power supplies by making use of printed inductors. Such components intent to replace the traditional transformer by suppling a reduced volume alternative. An investigation into these inductors is conducted and an implementation of its use is presented. The investigation led to conclude that the inductors may be used to provide isolation but further improvements into the fabrication process are required. Due to the current fabrication process involving impure silver as the conductor the resulting coils have a resistance excessively high. This creates difficulties in magnetic field creation as well as introducing a great level of losses. To solve this problem the presented implementation uses high frequency switching to allows for better results in the receiver side of the system.